ADMINISTRASI DAN SUPERVISI PENDIDIKAN ISLAM INTEGRASI BLEDED LEARNING KURIKULUM BERBASIS CINTA PADA MADRASAH IBTIDAIYAH - Nadia Eka Gusmaidawati; Siti Maulina Saputri; Ahmad Zainuri; Frika Farimah Zahra (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This article aims to analyze the role of Islamic educational administration and supervision in integrating blended learning with the Love-Based Curriculum (KBC) in Madrasah Ibtidaiyah. This integration is considered essential as an effort to address the challenges of 21st-century learning without neglecting compassion as the core value of Islamic education. A literature review is employed as the primary method to explore the concepts of Islamic educational management according to Prof. Dr. Ahmad Zainuri and to connect these concepts with the implementation of blended learning. The findings indicate that educational administration plays a significant role in planning, organizing, and implementing policies that support hybrid learning, while Islamic educational supervision ensures that the values of love (mahabbah), exemplary conduct, and spirituality remain the foundation of the learning process. The study confirms that effective governance and supervision are key determinants of the success of hybrid learning innovations based on Islamic values.